Microbe-host interplay in atopic dermatitis and psoriasis - Nanna Fyhrquist (Nature Portfolio, 2019)
Atopic dermatitis (AD) and psoriasis (PSO) are associated with dysbiosis. Here, by analyses of skin microbiome and host transcriptome of AD and PSO patients, the authors find distinct microbial and disease-related gene transcriptomic signatures that differentiate both diseases.